The Influence of Islamic Counseling on Drug Addiction Patients’ Quality of Life at the Qur’anic Healing Indonesia Rehabilitation Center - Izzah, Lailatul; Kurniawan, Willytiyo; Hamdi, Raspan; Nafisah A, Dini (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2025)
The widespread issue of drug abuse poses significant challenges to individuals' quality of life, particularly among those undergoing rehabilitation. This study investigates the effect of Islamic Counseling Guidance on the quality of life of drug addicts at the Qur’anic Healing Indonesia Rehabilitation Center. The study involved 90 male participants aged 20–35 years who had been in rehabilitation for more than three months. Total sampling was employed to include individuals classified as severe, moderate, and mild addicts. Data were collected using two reliable instruments: a Quality-of-Life Scale and an Islamic Counseling Scale (Cronbach’s Alpha > 0.90). The data were analyzed using simple linear regression. The findings indicated no significant influence of Islamic Counseling Guidance on quality of life (p = 0.934), suggesting that the Islamic counseling approach implemented in this setting was not effective in enhancing the patients’ quality of life. These results highlight the need to reevaluate and possibly integrate more holistic or tailored approaches in counseling interventions for drug rehabilitation.